Pendekatan Dakwah melalui Pemberdayaan Ekonomi Komunitas Berbasis Kearifan Lokal - Samsinas Samsinas (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
This study is related to the problem of the da’wah approach through community economic empowerment based on local wisdom with the object of research in the Bomba Batik craftsman community, Kamonji ward; (1) how is community empowerment based on local wisdom? (2) How can community economic empowerment be called a da’wah approach? The research used a descriptive qualitative approach and data analysis used a da’wah science and empowerment approach.Community empowerment is one form of Islamic da'wah approach. Because there are several models of social transformation that community empowerment has, namely; (1) Direct action transformation, (2) transformation collective action, (3) communal collaboration and (4) forming a market. Community economic empowerment based on local wisdom means empowerment based on wisdom values ​​that are born from the community itself so that the products produced are responded positively by the wider community.